1998
DOI: 10.1017/s0022112098003115
|View full text |Cite
|
Sign up to set email alerts
|

Circulation and formation number of laminar vortex rings

Abstract: The formation time scale of axisymmetric vortex rings is studied numerically for relatively long discharge times. Experimental findings on the existence and universality of a formation time scale, referred to as the 'formation number', are confirmed. The formation number is indicative of the time at which a vortex ring acquires its maximal circulation. For vortex rings generated by impulsive motion of a piston, the formation number was found to be approximately four, in very good agreement with experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
161
4
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 13 publications
23
161
4
1
Order By: Relevance
“…They assumed the physical process causing this constant formation number to be a maximum in total circulation attainable in the vortex ring. A numerical study by Rosenfeld et al (1998) demonstrates the invariance of this formation number to differences in the velocity programme and Reynolds number.…”
Section: Dependency Of Vectoring Behaviour On Strouhal Numbermentioning
confidence: 80%
“…They assumed the physical process causing this constant formation number to be a maximum in total circulation attainable in the vortex ring. A numerical study by Rosenfeld et al (1998) demonstrates the invariance of this formation number to differences in the velocity programme and Reynolds number.…”
Section: Dependency Of Vectoring Behaviour On Strouhal Numbermentioning
confidence: 80%
“…The universality of the formation number has been verified by a number of subsequent experimental (Dabiri & Gharib 2004a;Krueger, Dabiri & Gharib 2006;Pawlak et al 2007) and computational studies (Rosenfeld, Rambod & Gharib 1998;Mohseni, Ran & Colonius 2000). In particular, Rosenfeld et al (1998), Zhao, Frankel & Mongeau (2000) and Mohseni et al (2000), found the Reynolds number to have little impact on the formation number, provided that Re Γ is sufficiently large to ensure the formation process is completed before viscosity has a significant impact (Re Γ > 2000 according to Mohseni et al (2000)).…”
Section: Introductionmentioning
confidence: 85%
“…The Reynolds numbers considered here are comparable with those observed in jetting swimmers such as paralarval and juvenile squid (O'Dor 1988; Bartol et al 2009) and several species of jellyfish (Gladfelter 1973;Colin & Costello 2002;Peng & Dabiri 2009), which have been observed to operate at Reynolds numbers in the range of 10 2 -10 3 . We did not consider the effects of varying the Reynolds number, since they have been previously characterized for circular vortex rings, and found to have little impact on the formation number, in the intermediate range of Reynolds numbers (Rosenfeld et al 1998;Mohseni et al 2000;Zhao et al 2000).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An impulsive body force of this sort produces a leading vortex pair that pinches off from a trailing jet. The formation a the leading vortex ring (in the axisymmetric case) has been studied previously in experiments [25] and in computations that used a similar body force [21]. The toroidal radius of the ring is L and the leading ring is invariant to ␦ provided ␦/L is small.…”
Section: Two-dimensional Starting Jetmentioning
confidence: 99%